Formation of digital competences and skills of students in the transitional period of digital didactics (Journal of Educational Sciences, 2023)
The article analyzes the approaches of domestic and foreign researchers to the definition of theconcept of “digital didactics”. The distinctive features of traditional and digital didactics are presented,the characteristics of the new pedagogical branch are given and the main features of digital didacticsare highlighted. The result of the research is the introduction of an author’s online course on the discipline“Management of the learning process using DOT” for bachelor students of pedagogical specialties,which allowed the formation of digital competencies of students, expressed in the ability to analyze andestablish the qualitative compliance of a digital educational product with the goals and objectives; applyand adapt existing digital educational products to specific goals and objectives the learning process;independently extract and assimilate information, transform it according to the revealed patterns bymeans of modern technologies in the conditions of digitalization of the educational process. The formedcompetencies allowed students to take into account the changes taking place in the learning processassociated with the transformation of education. The article opens the beginning of a discussion in thefield of digital didactics in the system of higher pedagogical education and higher professional educationwithin the framework of the introduction of author’s developments aimed at the formation of the digitaleducational process, the implementation of new forms and methods of teaching.Key words: digitalization of education, digital didactics, digital learning, digital competencies, skills.